Mengatasi Data Error Pada Proses Data Cleaning Motion Capture Motive Optitrack - Selly Artaty Zega; Ahmad Saropi; Timothy Ronaldy; Yogi Ilhami; Muhammad Farabi (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2022)
Motion capture is a technology in the multimedia industry useful for recording movement in digital using a censor method. Motion capture technology is further developing time in time, motion capture is already used in some digital products like a game, visual effects, and animation films. on recording section motion capture its sight motion by the optical sensor or magnet sensor, next step is the data cleaning process, the data cleaning process will clean the movement noise or error. Using motion capture will make the production process faster because motion capture is not using the manual keyframe method. This article’s purpose is to help motive users to make the data cleaning process become faster with the research and development method. With data that has been collected in several recording processes, the writer hopes this article can be used as a guide in recording motion until the data cleaning process with motive application.